Kinetic properties and ignition characteristics of fuel compositions based on oil-free and oil-filled slurries with fine coal particles; Thermochimica Acta; Vol. 704 - Glushkov D. O. Dmitry Olegovich; Tabakaev R. B. Roman Borisovich; Altynbaeva D. B. Dariga Bakhitzhanovna; Nigay A. G. Aleksandr Gerasimovich (2020, 2020)
Title screen